2010
DOI: 10.1007/s00213-010-1799-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of kappa-opioid receptor ligands on prepulse inhibition and CRF-induced prepulse inhibition deficits in the rat

Abstract: Rationale Kappa-opioid receptor (KOR) agonists produce dysphoria and psychotomimesis in humans. KORs are enriched in the prefrontal cortex and other brain regions that regulate mood and cognitive function. Dysregulation of the dynorphin/KOR system has been implicated in the pathogenesis of schizophrenia, depression, and bipolar disorder. Prepulse inhibition of the acoustic startle reflex (PPI), a sensorimotor gating process, is disrupted in many psychiatric disorders. Objectives The present study determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…On the basis of preclinical data suggesting that cortisol levels may mediate the relation between KOR availability in this circuit and the behavioral expression of threat and loss symptoms, 27,28 we then examined the potential role of 24-hour urinary cortisol levels in mediating this association in humans. Given that PET imaging with the KOR-selective radioligand [ 11 C]LY2795050 allows one to assess KOR availability brain-wide, we additionally examined how [ 11 C]LY2795050 values in regions outside the amygdala-anterior cingulate cortexventral striatal neural circuit were related to threat and loss symptoms.…”
mentioning
confidence: 99%
“…On the basis of preclinical data suggesting that cortisol levels may mediate the relation between KOR availability in this circuit and the behavioral expression of threat and loss symptoms, 27,28 we then examined the potential role of 24-hour urinary cortisol levels in mediating this association in humans. Given that PET imaging with the KOR-selective radioligand [ 11 C]LY2795050 allows one to assess KOR availability brain-wide, we additionally examined how [ 11 C]LY2795050 values in regions outside the amygdala-anterior cingulate cortexventral striatal neural circuit were related to threat and loss symptoms.…”
mentioning
confidence: 99%
“…Bortolato et al [412] demonstrated that U50,488 disrupted PPI of the acoustic startle in rats, an effect reversed by atypical, but not typical, antipsychotic pretreatment. However, using various synthetic KOR agonists and salvinorin A, we found no effect of KOR activation on PPI [413]. Furthermore, KOR blockade did not alter basal PPI levels.…”
Section: Dyn/kors and Prepulse Inhibitionmentioning
confidence: 75%
“…The interactions between the KOR and CRF systems have been investigated heavily (Koob 2013, Land et al 2008, Tejeda et al 2010). The KOR and CRF systems have long been thought to interact in order to orchestrate anxiety-like responses.…”
Section: Interactions With Other Signaling Moleculesmentioning
confidence: 99%